Monitoring fatigue during the in-season competitive phase in elite soccer players - Thorpe, R. T.; Strudwick, A. J.; Buchheit, M.; Atkinson, G.; Drust, B.; Gregson, W. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To quantify the relationship between daily training load and a range of potential measures of fatigue in elite soccer players during an in-season competitive phase (17 d). Methods: Total high-intensity-running (THIR) distance, perceived ratings of wellness (fatigue, muscle soreness, sleep quality), countermovement-jump height (CMJ), postexercise heart-rate recovery (HRR), and heart-rate variability (Ln rMSSD) were analyzed during an in-season competitive period (17 d). General linear models were used to evaluate the influence of daily fluctuation in THIR distance on potential fatigue variables. Results: Fluctuations in fatigue (r = -.51, large, P < .001), Ln rMSSD (r = -.24, small, P = .04), and CMJ (r = .23, small, P = .04) were significantly correlated with fluctuations in THIR distance. Correlations between variability in muscle soreness, sleep quality, and HRR and THIR distance were negligible and not statistically significant. Conclusions: Perceived ratings of fatigue and Ln rMSSD were sensitive to daily fluctuations in THIR distance in a sample of elite soccer players. Therefore, these particular markers show promise as simple, noninvasive assessments of fatigue status in elite soccer players during a short in-season competitive phase.